Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian Pelanggan Produk Somethinc E-Commerce Tiktok Shop - Moza Ananta; Arry Dwi Syahputra (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
Purpose to analyze the effect of price and product quality on purchase decision for product Somethinc at E-Commerce Tiktok Shop. This research is included in the category of causal associative research using a quantitative approach. The population of this study were buyers of Somethinc products at the E-Commerce Tiktok Shop. The sampling technique used incidental sampling technique. The analytical method uses simultaneous and partially linear regression analysis. The results of the research show that in simultaneous and partially ways price and product quality have a positive and significant effect on the purchase decision for product Somethinc at E-Commerce Tiktok Shop